Factors affecting customers’ adoption of fintech in the gulf cooperation council countries - Shehata, Saleh Mohamed; Abdeljawad, Alaa Mohamed; Mazouz, Loqman Abdelkader; Aldossary, Lamia Yousif Khalaf; Alsaeed, Maryam Yousif; Sayed, Mohamed Noureldin (Asian Economic and Financial Review, 2023)
This study examines the factors affecting customers’ adoption of fintech in the Gulf Cooperation Council (GCC) countries. Based on fintech adoption models, a conceptual framework was developed and extended to include COVID-19 situational influences. Data were collected during the spread of COVID-19 and its subsequent variants. The sample comprises 484 customers who obtained financial services in the GCC countries. Hypotheses were tested using partial least squares structural equation modeling (PLS-SEM). The findings indicate that perceived usefulness, perceived ease of use, trust, and situational influences of COVID-19 have significantly affected customers’ attitudes toward the use of fintech. Furthermore, such attitudes had a significant effect on customers’ intentions to use fintech. The findings also indicate that both perceived usefulness and the situational influences of COVID-19 have had significant direct and indirect effects on customers’ intentions to use fintech. Social influences have only directly affected customers’ intentions to use fintech, both perceived ease of use and trust have only indirectly affected the customers’ intentions to use fintech. Conversely, the findings show that social influence does not affect customers’ attitudes towards using fintech. This study provides several recommendations to financial institutions in the GCC Countries.